Effect of a 2-week interruption in methotrexate treatment versus continued treatment on COVID-19 booster vaccine immunity in adults with inflammatory conditions (VROOM study): a randomised, open label, superiority trial - Abhishek, A; Boyton, RJ; Peckham, N; McKnight, Á; Coates, LC; Bluett, J; Barber, V; Cureton, L; Francis, A; Appelbe, D; Eldridge, L; Julier, P; et al. (Elsevier, 2022)
Background Immunosuppressive treatments inhibit vaccine-induced immunity against SARS-CoV-2. We evaluated whether a 2-week interruption of methotrexate treatment immediately after the COVID-19 vaccine booster improved antibody responses against the S1 receptor-binding domain (S1-RBD) of the SARS-CoV-2 spike protein compared with uninterrupted treatment in patients with immune-mediated inflammatory diseases.